The Effect of Tempeh on the Ability of Macrophage Phagocytosis An experimental study in male Balb/c mice - Afiyata, Noven; Sarosa, Hadi; Sumarawati, Titiek (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Consuming tempeh regularly increases the levels of isoflavones in the our body influencing the IFNã and macrophage activating factor (MAF) that lead to the in increase in the ability of macrophage phagocytosis. Macrophage phagocytosis gives an illustration of the macrophages ability as the first line of phagocytic cells to digest foreign particles. This study aims at finding out the influence of tempeh on the ability of macrophage phagocytosis.Design and Methods: In an experimental study using post test only control group design, 15 mice Balb/c were divided into 3 groups of 5 mice each. Gp1: 0.5 gr of tempeh juice, Gp2: 1 mg tablet imboost in 1 cc of water (positive control), Gp3: 1 cc of 1 times (negative control). Treatment was given daily for 12 days. On day 13, Phagocytic ability of macrophages were examined using latex beads method. Data were analyzed using one Kruskal Wallis test followed by Independent T-Test.Results: The phagocytic ability for the three groups were 760,6 —–± 109,898 ; 244.2 ± 70.159; 9.6 ± 2.839 respectively. Independent t- test resulted in the significance difference (p = 0.008) between treated groups and control groups, both positive and negative ones (p<0,05).Conclusion: There is a difference in phagocytic ability between treatment and control groups (Sains Medika, 3(1):54-62).